Adaptive Performance in Public Sector Reform: Psychological Capital and Work Engagement - Dini Aprilia Palupi; Riani Rachmawati (Goodwood Publishing, 2026)
Purpose: This research is intended to analyze how psychological capital influences adaptive performance among civil servants affected by bureaucratic simplification, both directly and indirectly through work engagement. The analysis focuses on adaptive performance at the dimensional level to identify specific psychological mechanisms operating in a public sector reform context. Research Methodology: The study was conducted at the Coordinating Ministry for Economic Affairs, Indonesia, using a quantitative cross-sectional survey design. Data were gathered from 165 civil servants whose positions shifted from structural to functional roles following bureaucratic reform. Psychological capital was measured using the Compound Psychological Capital Scale (CPC-12), work engagement using the Utrecht Work Engagement Scale (UWES-9), and adaptive performance using a multidimensional adaptive performance scale. Structural equation modeling (SEM) with SmartPLS was employed to analyze the data. Results: Psychological capital significantly enhances work engagement and positively affects all dimensions of adaptive performance. However, work engagement does not significantly influence interpersonal adaptability and training effort. Consequently, work engagement only partially mediates the relationship between psychological capital and adaptive performance. Conclusions: Psychological capital plays a central role in strengthening adaptive performance during bureaucratic simplification, although engagement operates unevenly across adaptive dimensions. Limitations: The findings should be interpreted with caution due to the cross-sectional design and single-organization context, which may limit causal inference and generalizability. Additionally, the use of self-reported data in this study may introduce potential bias. Contributions: This study extends psychological capital theory to public sector reform and provides dimensional-level evidence relevant to public administration and human resource development.